(untitled) (International Journal of Ayurveda and Pharma Research, 2025)
The study compares the Colony Forming Units (CFU) of prepared and market samples of three Aristas: Abhayarista, Balarista, and Jeerakarista, which are fermented Ayurvedic medicines. Aristas naturally generate alcohol through fermentation facilitated by yeast found in Woodfordia fruticosa Kurz, with Jaggery serving as the sugar source. The fermentation process spans 30-45 days, during which complete sugar utilization ensures optimal results. Incomplete fermentation, however, can cause post-fermentation issues and acidity development. The microbial fermentation process is characterized by distinct growth phases: a lag phase for acclimatization, a log phase for exponential growth, a deceleration phase due to reduced energy reserves, and a stationary phase where microbial activity stagnates but viability is maintained. The presence of residual sugar can trigger renewed fermentation cycles, leading to post-fermentation challenges. For this analysis, three samples of prepared Aristas and five corresponding market samples from the Kerala market were tested. CFU was assessed using the Mueller-Hinton agar method, and statistical evaluation employed a one-sample t-test. The results revealed a significant difference in CFU levels in two of the market samples (p < 0.01), while the remaining samples showed no significant variation (p>0.05). This study highlights the variability in CFU between prepared and market samples, emphasizing the importance of consistent fermentation processes in ensuring the quality of Ayurvedic fermented medicines.